Migration brokerage, illegality, and the state in Anglophone Cameroon - Maybritt Jill Alpes (Danish Institute for International Studies (DIIS), 2013)
Migration brokers are important participants within the increasingly commercialized policing of borders. Focusing on connections between migration brokers and state authorities, this paper asks how migration brokers relate to the realm of the law, as well as how the law relates to migration brokerage. By examining illegality only when it becomes visible to aspiring migrants and brokers within their context of departure, this paper demonstrates how state regulation is intimately intertwined with the emergence of migration brokerage. The argument of the paper provides a counter-point to studies of migration and illegality that often adopt an implicitly statist perspective by categorising brokers as either legal or illegal, as well as by framing brokers as agents that work 'against' the state. The paper is based on fourteen months of ethnographic fieldwork in Anglophone Cameroon between 2007 and 2010 and illuminates the work of two NGOs that engage in so-called 'travel consultations'. It contributes to on-going discussions within the 'Migration Industry and Markets for Migration Control Network'.
Keywords: 300